Main social vulnerability indicators in the COVID-19 pandemic in Iran - Moslehi, Shandiz; Dehdashti, Alireza; Pourmohammdi, Behrad; Fatemi, Farin (Frontiers in Public Health, 2023)
Background Social factors play the main role in the vulnerability of exposed countries to disasters. The COVID-19 pandemic as a disaster is not an exception to this fact. This study aimed to determine the main social vulnerability indicators in the COVID-19 pandemic in Iran. Methods This study was conducted during the period of 2021–2022 in three phases, including a systematic review, a virtual panel expert, and the Analytical Hierarchy Process. First, the draft of social vulnerability indicators in COVID-19 was extracted through a systematic review. Then, the extracted indicators were finalized and prioritized by the expert panel and the AHP, respectively. Results Initially, the literature review found five domains and 38 indicators of social vulnerability in COVID-19. The outcome of the expert panel increased the related domains to six but decreased the indicators to 31. The three prioritized social vulnerability indicators that were determined by the AHP were population density, accessibility to healthcare facilities, and relevant services and vulnerable groups. Conclusion Measuring social vulnerability with the identified indicators is valuable for addressing high COVID-19 incidence among socially vulnerable hotspot areas. Regarding the result of this study, further research should be conducted to validate the identified indicators.